The Implementation of Air Facilitation (FAL) Activities in Juanda-Surabaya International Airport - Ajun Dwi Handayani; Dinar Dewi Kania; Suharto Abdul Majid (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The purpose of this study is to determine the priority of improving the implementation of Air Facilitation (FAL) activities at CIQ (Customs, Immigration, and Quarantine) at Juanda International Airport, Surabaya. The analytical method uses AHP (Analytic Heirarchy Process) analysis. Data obtained through interviews with 5 (five) experts and questionnaires to 10 (ten) people consisting of 5 (five) experts and 5 (five) CIQ (Customs, Immigration, and Quarantine) officers at Surabaya International Airport. The results showed that the Air Facilitation (FAL) activities in the CIQ Section of Juanda International Airport in Surabaya had been going well, but specifically considering the limited space / place in the terminal, the implementation of the Facilitation function (FAL) at the Airport still need to be further improved. The results of  the analysis process by AHP analysis based on data processing with expert choice software weighting on the customs sub-criteria (customs) contained in the departure facilitation at T1 (service and monitoring posts are too narrow and TPS is not available and the area for K-9 placement), Swallow Toilet and control room.